Congenital choledochal cyst - Heyder bin Heyder (Paediatrica Indonesiana, 1973)
Although congenital choledochal cyst, a localized dilatation of the common bile duct, is an unusual condition in many countries, it should be expected in any infant who presents the triad of jaundice, tumor and pain in the right upper abdomen. Not less than 500 cases have been reported in the medical literature. Recently it is pointed out, that the congenital chledochal cyst is more common in Japan than in Europe or American countries. A personal contact with the Japanese delegation attending the meeting of the Pacific Association of Pediatric Surgeons in Vancouver, May 1971, confirmed it.